PENGARUH BAURAN PEMASARANTERHADAP KEPUTUSANPEMBELIAN BATIK DI USAHA KECIL MENENGAH BATIK SURAKARTA - Erna Tiningrum (ADVANCE, 2014)
The purpose of this study was to investigated the influence of product, price, place, and promotion of the purchasing decisions in the Small and Medium Enterprises Batik Surakarta City. Techniques of data analysis using multiple linier regression analysis,t-test, R2-test. The method used for data collection was based on questionnaires distributed to 100 buyers batik in the Small and Medium Enterprises (SMEs) Batik Surakarta City. With the result of the (X1) Product has positive and significant impact onpurchasing decisions in the Small and Medium Enterprises Batik Surakarta City. (X2) Price has positive and significant impact on purchasing decisions in the Small and Medium Enterprises Batik Surakarta City, . (X3) Place has positive and significant impact on purchasing decisions in the Small and Medium Enterprises Batik Surakarta City, . (X4) Promotion has positive and significant impact on purchasing decisions in the Small and Medium Enterprises Batik Surakarta City.Promotion of factors have contributedthe most powerful in influncing buying decisions at the Small and Medium Enterprises Batik Surakarta City, compared with the other variables. The magnitude of the effect of variable product, price, place, and promotion .(Adjusted R2) of purchasing decisions in the Small and Medium Enterprises Batik Surakarta City at 81.3%, while 18.7% is influenced by other factors beyond the variable. Keyword: Product, Price, Place, Promotion, and Purcashing Decisions